Second record and range extension of the one‐jaw eel, Monognathus jesse , from the northeastern Pacific Ocean (Anguilliformes: Monognathidae) - Benjamin W. Frable; Dahiana Arcila; C. Anela Choy (Journal of Fish Biology, 2026)
Herein, we report the second known specimen of the one‐jaw eel, Monognathus jesse , collected in 4200 m of water, between 1748 and 2001 m depth, in the northeastern Pacific. This specimen is the second‐largest identified monognathid specimen reported, with a total length of 154 mm unpreserved. A morphological description, comparison to the much smaller holotype and similar species, a micro‐computed tomography scan, and mitochondrial sequences are provided. This specimen also represents a 3200 km northeastern range extension for the species, as the holotype was recovered 1050 km southeast of Hawai'i. A phylogeny of cytochrome oxidase‐I for this and related eel species recovers Monognathus as the sister to a clade comprising Cyema , Saccopharynx and Eurypharynx, contrasting previous hypotheses.

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

A New Species of the Eel Genus Gnathophis (Congridae, Anguilliformes) from the Seamounts of the Emperor–Hawaiian Chain, Western and Central North Pacific - Artem M. Prokofiev; Benjamin W. Frable; Olga R. Emelianova; Svetlana Yu. Saveleva; Alexei M. Orlov (Journal of Marine Science and Engineering, 2025)
Gnathophis johnsoni sp. nov. is described on the basis of 15 specimens (138–380 mm TL) from the Emperor–Hawaiian Seamount Chain in the western and central North Pacific. The new species is most similar in morphology to G. bathytopos (Atlantic), G. cinctus (eastern Pacific), and G. smithi (Nazca and Salas-y-Gomez Seamounts in the southeastern Pacific) by the sensory pore configuration and vertebral count, but differs from these species in the following characters in combination: darkly pigmented pectoral fin, dorsal fin with black margin broadened caudally and extended onto the distal half of the caudal fin, relatively long head, jaws, gill slit and caudal fin, and on average a greater preanal distance. Although most of morphometrics overlap between the new species and its closest relatives, multivariate statistical analyses clearly discriminate this species. Molecular analysis shows sister relationships between the new species and G. cinctus, with 1.81% of genetic divergence, which significantly exceeds the differences between the haplotypes belonging to the same species (0.36 and 1.08% of divergence, usually not exceeding 0.9%) and confirms both species as close but distinct. The close relationship of G. johnsoni sp. nov. and G. cinctus represents a rare case of biogeographical relations between western and eastern Pacific demersal fish faunas. Molecular data suggest that some morphologically similar species may represent independently evolved lineages, though the group of Gnathophis possessing elevated lateral-line pores is likely monophyletic.

Heterochrony and the evolution of the longjaw mudsucker (Gobiidae, Teleostei) - Jimjohn Milan; Tyler Fidel; Watcharapong Hongjamrassilp; Benjamin W. Frable; Zachary R. Skelton; Philip A. Hastings (Journal of Fish Biology, 2024)
Although longjaw mudsucker ( Gillichthys mirabilis , Gobiidae) has been studied extensively for its ability to occupy low‐oxygen environments, few studies have addressed the evolution of its exceptionally elongated jaws that extend posteriorly beyond the gill opening in large adults. In this study, the ontogeny of the maxillae of G. mirabilis , Gillichthys seta , and the out‐group species Eucyclogobius newberryi was studied within the heterochrony framework using digitized landmarks and caliper measurements. The results show that the maxilla of both species of Gillichthys evolved via acceleration (increased growth rate) and that of G. mirabilis via hypermorphosis (continued growth to a larger body size); two forms of peramorphosis. This is in contrast to earlier studies that concluded that G. seta is paedomorphic. We were unable to confirm an earlier hypothesis of sexual dimorphism in the jaw length of G. mirabilis . The evolution of the elongated jaws and associated large buccopharyngeal membrane in G. mirabilis is hypothesized to increase the surface area for gas exchange during aerial respiration and may also serve to amplify the aggressive gaping display as observed in other fishes.

Widespread occurrence and repeated evolution of ultra-black camouflage in the pelagic deep-sea anguilloid eels (Anguilliformes) - Michael J. Ghedotti; Kandice C. Agudo; Flor M. Gonzalez; Benjamin W. Frable (Environmental Biology of Fishes, 2023)

Two’s company: first record of two free-swimming megamouth sharks, Megachasma pelagios (Lamniformes: Megachasmidae), off the California coast - Zachary R. Skelton; Dovi Kacev; Benjamin W. Frable; Andrew Chang; Valentin Costescu; David Stabile; David A. Ebert (Environmental Biology of Fishes, 2023)
On September 11, 2022, two megamouth sharks ( Megachasma pelagios ), estimated at 3.7–4.6 m TL, were observed swimming together near the surface about 39 km off the coast of San Diego, CA, USA. Megamouth sharks are rarely observed pelagic sharks, and the film from this encounter provided new insight into the social behavior of this species. We attempt to put the behavior of these two individuals into the context of past sightings, known megamouth shark biology, and with analogous behavior observed in other shark and pelagic fish species.

Biogeographic reconstruction of the migratory Neotropical fish family Prochilodontidae (Teleostei: Characiformes) - Benjamin W. Frable; Bruno F. Melo; João P. Fontenelle; Claudio Oliveira; Brian L. Sidlauskas (Zoologica Scripta, 2022)
Geographically, widespread Neotropical fish lineages offer opportunities to reconstruct historical biogeography patterns and infer processes leading to modern ichthyological diversity and distribution. The characiform family Prochilodontidae is well suited for such reconstruction because their migrations limit population substructure within river systems. Therefore, their biogeographic history should match closely the history of connectivity among Neotropical river basins. Here, we combine a time‐calibrated phylogeny with biogeographic model testing to recover the history of this family's diversification. Results support the Miocene rise of the Andean Eastern Cordillera as a dispersal barrier, but also indicate a much earlier Eocene origin of the trans‐Andean genus Ichthyoelephas . Despite the early origin of the family and its three constituent genera, most prochilodontid lineages originated during the Miocene in Greater Amazonia, likely due to drainage reorganizations caused by Andean uplift. Subsequent speciation appears linked to interbasin exchanges and expansions of Amazonian lineages into Brazilian coastal systems. The modern richness of Prochilodus in easterly drainages appears to be relatively young, with only Prochilodus vimboides likely reaching that region prior to the late Miocene. The rise of the Vaupes Arch coincides with two splits between Orinocoan and Amazonian lineages circa 9 million years ago (Ma). However, two instances of later dispersal between these drainages reveal the permeability of the Vaupes Arch, suggesting that it may promote periodic speciation. This study illustrates how model‐based biogeographic studies of widespread groups can reconstruct historic paths of dispersal and help reveal how landscape evolution promoted modern diversity patterns.

A new maximum size for the family Nomeidae and the third record of a longfin cigarfish, Cubiceps paradoxus (Stromateoidei: Nomeidae) from California, USA - Benjamin W. Frable; Merit H. Mccrea; Milton S. Love; Matthew T. Craig (Journal of Fish Biology, 2020)
We report the largest specimen from the stromateoid family Nomeidae. The specimen, measuring 1283 mm total length unpreserved, was caught on hook and line from shore in Port Hueneme, California, USA in June 2019. Despite scavenging damage, the specimen was identified as a longfin cigarfish, Cubiceps paradoxus, using morphological characters and molecular techniques. This is the third record of C. paradoxus from California. We also provide an account of a previously unreported C. paradoxus collected off the US‐Mexico Border in 1999 that was examined but not preserved.

A new species of grouper, Epinephelus craigi (Perciformes: Epinephelidae), from the South China Sea - Benjamin W. Frable; Sarah J. Tucker; H. J. Walker (Ichthyological Research, 2019)